2019
DOI: 10.1016/j.ymthe.2018.10.015
|View full text |Cite
|
Sign up to set email alerts
|

LDR-Induced miR-30a and miR-30b Target the PAI-1 Pathway to Control Adverse Effects of NSCLC Radiotherapy

Abstract: Radiotherapy has been a central part in curing non-small cell lung cancer (NSCLC). However, it is possible that not all of the tumor cells are destroyed by radiation; therefore, it is important to effectively control residual tumor cells that could become aggressive and resistant to radiotherapy. In this study, we aimed to investigate the molecular mechanism of decreased NSCLC radioresistance by low-dose radiation (LDR) pretreatment. The results indicated that miR-30a and miR-30b, which effectively inhibited p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…It has been widely reported that miRNAs can participate in the progression of cancers through modulating its downstream target genes [41][42][43] . From this point, we discovered that miR-217 harbored the binding sites for both KCNQ1OT1 and ZEB1.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely reported that miRNAs can participate in the progression of cancers through modulating its downstream target genes [41][42][43] . From this point, we discovered that miR-217 harbored the binding sites for both KCNQ1OT1 and ZEB1.…”
Section: Discussionmentioning
confidence: 99%
“…Six-week-old male C57BL/6 mice (Orient Bio, Seongnam, Korea) were used for the in vivo experiments following the previous study [ 26 ]. The protocols used were approved by the Institutional Animal Care and Use Committee of Pusan National University (Busan, Korea) and performed in accordance with the provisions of the NIH Guide for the Care and Use of Laboratory Animals.…”
Section: Methodsmentioning
confidence: 99%
“…Radiation therapy combined with chemotherapy can produce a cure only in a small number of NSCLC patients because NSCLC is comparatively less sensitive to chemotherapy or radiation (4,5). Acquired resistance results in local tumor recurrence or failure of radiotherapy (6,7). Increasing evidence has demonstrated that epithelial-to-mesenchymal transition (EMT) mediated tumor metastasis is closely associated with radiation resistance (8,9).…”
Section: Introductionmentioning
confidence: 99%